Multi-agent-based simulation XV : International Workshop, MABS 2014, Paris, France, May 5-6, 2014, Revised selected papers /: International Workshop, MABS 2014, Paris, France, May 5-6, 2014, Revised selected papers. (2015) - Unknown
No abstract available